Rethinking Mindfulness in Education within Two Frameworks: Articulating the “Threefold Model of Mindful Wisdom” with the “Theory of Mental Interference” - Kamala Klebanova (Religions, 2022)
The existent trend of implementing mindfulness-based programs (MBPs) into public education came along with an increasing scientific record regarding the definitional construct of mindfulness, effects of various mindfulness-based interventions and their basic mechanisms. In terms of the rising definitional discourse in the interdisciplinary field of mindfulness, the “threefold model of mindful wisdom” (TMMW) was proposed. In the present paper’s quest of rethinking mindfulness in education, the relevance of the TMMW for didactics in modern Western educational systems (with special interest on the region of Germany) is examined, affirmed in several points and—with the aid of the “Theory of Mental Interference” (TMI)—methodically linked to individual learners’ needs. The TMI has been developed at the University of Hamburg since 1984 by Wagner and colleagues. This is compatible with the TMMW with regard to the concept of self and basic psychological mechanisms of “mindful exercises”. Its basic approach conceives the epistemic level of cognitive processes (1) to be unbiased by affect and (2) to be different from a level of mental interference, which in case of an arising default habitually interferes with the cognitive processes. Implications for further research, for modern educational systems and for MBPs in education are discussed.